Analisis dan Perancangan Sistem Informasi Sebagai Penunjang Keputusan pada UKM PD Gerak Tani Jakarta - Pelawi, Dewan (ComTech: Computer, Mathematics and Engineering Applications, 2011)
To maintain a trading business in the strict competition a management supported by appropriate business strategy is required. Utilization of an information system that supports decision-making is needed to improve performance as well as support for all lines of business. Therefore, a research is conducted that specifically aims at the development of decision support systems for small and medium enterprises (SMEs). The basic method for building the system is the Herbert Simon's four-stage decision-making approach: intelligence, design, choice and implementation. Following is the building of data management subsystem, management subsystem model and user interface subsystem. The development of this system results in a decision support system that can improve the performance of all business lines complemented with support information for decision making.